Synthesis and Antibacterial Activity of N-phenyl-3-(4-chlorophenyl)-5-(3,4-dimethoxy-phenyl) pyrazoline - Nofiyanti, Estin; Wahyuningsih, Tutik Dwi; BTAG, Noer Laelly; Anwar, Chairil; Nurjanah, Novi; Salman, Nurcholis; Priastomo, Yoga (Molekul, 2025)
ABSTRACT. Compound of N-phenyl-3-(4-chlorophenyl)-5-(3,4-dimethoxy-phenyl) pyrazoline was synthesized by cycloaddition reaction. The structure of the product was chracterized by FTIR, 1H-NMR and 13C-NMR spectrometers. The pyrazoline was screened for antibacterial activity using agar diffusion method against Staphylococcus aureus, Bacillus cereus, Bacillus subtillis, Shigella flexnerri, and Escherichia coli. The pyrazoline had been synthesized from chalcone with phenylhydrazine to give 52.90% yield. Antibacterial screening showed that pyrazoline was active against selected gram positive bacteria. The pyrazoline was found to exhibits an antibacterial activity and its zone of inhibition/concentration against S. aureus (8.75/300), B. cereus (7.75/1000), B. subtillis (6.50/1000), and E. coli (3.50/300). The result showed that pyrazoline which was subtituted with chloro and methoxy, was able to posse broad spectrum of the tested pathogenic bacteria. Keywords: chalcone, pyrazoline, antibacterial